Plasma malondialdehyde levels related to acne vulgaris severity - Puspita, Fitri; Jusuf, Nelva Karmila; Yosi, Ariyati (UI Scholars Hub, 2021)
Background: Acne vulgaris (AV) is a multifactorial disorder characterized by the formation of open and closed comedones, papules, pustules, nodules, and cysts. Oxidative stress plays a role in the pathogenesis of AV. Reactive Oxygen Species (ROS), especially lipid peroxides (LPO), plays a role in mediating acne inflammation. Malondialdehyde (MDA) is one of the byproducts of LPO commonly used as a biomarker of cell damage.Methods: This cross-sectional analytic study consisted of sixty patients with AV. The samples were taken from the blood plasma of AV subjects. An enzyme-linked immunosorbent assay (ELISA) examination was performed. The normality of data distribution was determined using the Kolmogorov-Smirnov test and the differences of plasma MDA levels based on the severity of AV were determined using the Kruskal-Wallis test. P valueResults: Acne vulgaris was predominantly found in women (70%), age group of 18 – 25 years old (73,33%), and patients with family history of AV (61,67%). Higher plasma MDA levels were found in women [5,5 (2,53 – 77,6) nmol/mL], age group of 26 – 35 years [5,66 (2,73 – 25) nmol/mL], and subjects with family history of AV [5,49 (2,53 – 77,6) nmol/mL]. Based on the severity of AV, the severe AV group had highest plasma MDA [13,85 (2,69 – 77,6) nmol/mL], followed by moderate AV group [4,46 (2,53-14,3) nmol/mL] and mild AV [3,78 (2,47-6,88) nmol/mL]. There were differences in plasma MDA level based on the severity of AV (p<0,001).Conclusion: There were differences in plasma MDA levels based on the severity of AV.